HUBUNGAN DUKUNGAN KELUARGA DENGAN KONSEP DIRI PENDERITA TUBERKULOSIS PARU - Selfita Wahyu; Sofiana Nurchayati; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Pulmonary Tuberculosis is the 9th cause of death in the world. The family plays a role in caring for sick familymembers, the individuals in the family make the family as hope, get information and help get treatment. Thepurpose of this research to determine the relationship between family support fo r the pulmonary tuberculosispatient and self-concept. This research used descriptive correlation design with cross sectional method.Sample of this reaserch are 49 respondents drawn based on inclusion criteria. This research using purposivesampling techniques. Data was collected by using questionnaire of family suppor and self -concept. Dataanalysis is done by univariat and bivariat analyze with chi suare test. The results shows the majority are late asmany as 31 people (63,3%), the majority of respondents are male as many as 36 people (73.5%), the majorityof respondents are wiraswasta status as 28 (57,1%) with the majority of last education is senior hight school asmany as 25 people (51.0%), based on responden characteristic the majority of respondent s have tuberculosisless then 6 month as 33 people (67,3%). The majority of respondents who have hight family support amountedto 30 (61,2.9%) and the majority of respondents who have positive self -concept as many as 27 people (55,1%).Result of this research show that there is relationship between family supoort and self -concept with p value(0.003) < α (0.05). The results of this research recommends that families can be a support system to providemotivation and encouragement that as to facilitate and provide information on the treatment about drugcompliance to tuberculosis patien’s.Keywords: Celf-concept, Family support, Tuberculosis